Forest management in northern Fennoscandia: the need for solutions that mitigate conflicts during forest regeneration and increase the use of continuous cover forestry - Ersson, Back Tomas; Hansson, Linnea; Manner, Jussi; Sandström, Per; Sonesson, Johan (2023)
Today, conflicts often occur in northern Fennoscandia (also known as Sápmi) between forestry and reindeer husbandry. Continuous cover forestry (CCF) is requested by both reindeer herding communities and the general public and is becoming more common, but the forest industry criticizes CCF for lower wood production. Mechanical site preparation (MSP) increases regeneration success and, thus, increases wood production in CCF. To reduce the conflict between forestry and reindeer husbandry, MSP in Sápmi should destroy as little ground lichen as possible. Today, there are no solutions for gentle and lichen-adapted MSP in CCF. Thus, there is a strong need to develop and test new technical solutions that increase regeneration success in a lichen-adapted way during CCF in Sápmi. We suggest that MSP solutions be developed which are gentle, work selectively and function in shelterwoods, gap cuts, and selection cutting stands. We envision that these solutions could fill the gap between the desired adaptivity on the part of the reindeer herding communities and the desired efficiency on the part of the forest industry. Such MSP technology would contribute to increased acceptance of CCF in the forest industry, higher biodiversity, and considerably reduce the conflict between forestry and reindeer herding communities.